THE EFFECT OF PRE-TEXT QUESTIONS ON PREPARING STUDENTS FOR THE TEXT - (:unkn) unknown (INTL INST SOCIAL & ECONOMIC SCI, 2019)
In order to enable the students to reach the determined goals, while preparing questions based on the texts, the questions should be grouped into the questions to be asked before the text, the questions to be asked while the text is processed and the questions to be asked after the text is processed, and the levels of these questions should be organized according to the performance of the students. Akyol (1997) defines the limitations of the text preparation questions as pre-text questions can limit the understanding of the reader because the reader can only read to find the answers to the questions ; while the advantages of these questions pre-text questions arouse curiosity about the material to be read by the student; It focuses its attention on specific information and makes it easier to make accurate interpretations of what might happen next stage. Based on these approaches, this research was aimed to examine the effect of pre-text questions on preparing students for the text. 60 (29 male, 31 female) students of the second grade students in Sancaktepe district of Istanbul participated in the study. In the study, which was designed according to the case study of qualitative research patterns, as a data collection tool, student worksheets consisting of pre- and post-text questions prepared by the researchers, observation notes and semi-structured interview form were used. The practice was carried out with two narrative texts prepared with 5W-1H questions (the first text formed by giving 5W-1H questions before the text, the second text formed by giving 5W-1H questions after the text) and the form of I Choose Worksheet after the course. Content analysis was used to analyze the collected data. As a result of the findings, it was observed that the students wanted to ask questions about the pre-text, the questions asked led them to understand the text better and they preferred the text consisting of pre-text questions.
Keywords: Pre-text questions; post-text questions; 5W-1H questions; narrative text; preparation for the text; COMPREHENSION; KNOWLEDGE